2021
DOI: 10.3390/chemosensors9090271
|View full text |Cite
|
Sign up to set email alerts
|

Label Free, Lateral Flow Prostaglandin E2 Electrochemical Immunosensor for Urinary Tract Infection Diagnosis

Abstract: A label-free, rapid, and easy-to-use lateral flow electrochemical biosensor was developed for urinary tract infection (UTI) diagnosis in resource challenged areas. The sensor operates in non-faradaic mode and utilizes Electrochemical Impedance Spectroscopy for quantification of Prostaglandin E2, a diagnostic and prognostic urinary biomarker for UTI and recurrent UTI. To achieve high sensitivity in low microliter volumes of neat, unprocessed urine, nanoconfinement of assay biomolecules was achieved by developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In previous reports, electrochemical sensors of prostaglandin E1 (Zheng et al, 2016) and 8-iso-prostaglandin F2α (Sanchez-Tirado et al, 2017) have been successively reported. With the deepening understanding of the fatty acid derivative hormone and the development of electrochemical sensors, Ganguly et al (2021) developed a three-electrode planar gold microelectrode system with flow-based nanopore membranes for electrochemical immunosensors for detecting prostaglandin E2 (PGE2). This sensor can be used in both clinical and home settings for a more immediate, fast and accurate diagnosis of urinary tract infection.…”
Section: Electrochemical Sensors For the Detection Of Fatty Acid Deri...mentioning
confidence: 99%
“…In previous reports, electrochemical sensors of prostaglandin E1 (Zheng et al, 2016) and 8-iso-prostaglandin F2α (Sanchez-Tirado et al, 2017) have been successively reported. With the deepening understanding of the fatty acid derivative hormone and the development of electrochemical sensors, Ganguly et al (2021) developed a three-electrode planar gold microelectrode system with flow-based nanopore membranes for electrochemical immunosensors for detecting prostaglandin E2 (PGE2). This sensor can be used in both clinical and home settings for a more immediate, fast and accurate diagnosis of urinary tract infection.…”
Section: Electrochemical Sensors For the Detection Of Fatty Acid Deri...mentioning
confidence: 99%
“…For quantifying inflammation, urine has been widely studied in the research space, mainly because it is easily accessible, is “quiescent” since the molecular activity does not change much after sampling and does not require specialized sampling by trained professionals, and hence can be easily deployed for home-based routine screening [ 1 , 5 ]. There has been a great advancement in the field of POC diagnostic devices for inflammatory and infectious diseases in the current research space for a home-based multiplexed detection of biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The transduction of the antibody-antigen binding event is achieved by monitoring the interfacial modulation of the electrode-urine interface as a function of the binding. The sensor is in the form of a standard planar gold three-electrode electrochemical system on a flexible, nanoporous lateral flow membrane substrate [ 5 , 13 ]. The porosity of the substrate allows for a wide dynamic range and enhanced sensitivity due to the phenomena and macromolecular crowding which is especially important for developing ultrasensitive sensors for detecting cytokines that are expressed in very low concentrations in biofluids [ 4 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…24,25 Thus, PGE2 was chosen as the target biomarker to achieve early, accurate single number quantitative readouts, independent of the causative pathogen. 26 To produce a costeffective, portable, rapid diagnostic device, electrochemical/ electroanalytical methods were chosen as the transduction mechanism for biosensing. Electrochemical biosensors are popular for building POC devices as they are (i) small, portable, mass-producible, and inexpensive as they are compatible with microfabrication and (ii) are reliable as they seamlessly integrate with miniaturized electronics with high fidelity and are generally programmed to give out quantitative results.…”
mentioning
confidence: 99%
“…In their recent work, Ebrahimzadeh et al showed that urinary Prostaglandin E2 (PGE2) is one such biomarker that can serve not only as a reliable diagnostic but also a prognostic biomarker for rUTI in postmenopausal women . PGE2, which is an enzymatic product of cyclooxygenase-2 (COX-2), is a critical mediator of the inflammatory response. , Thus, PGE2 was chosen as the target biomarker to achieve early, accurate single number quantitative readouts, independent of the causative pathogen . To produce a cost-effective, portable, rapid diagnostic device, electrochemical/electroanalytical methods were chosen as the transduction mechanism for biosensing.…”
mentioning
confidence: 99%